Assessment of polygenic architecture and risk prediction based on common variants across fourteen cancers - Yan Dora Zhang (Nature Communications, 2020)
In cancer many gene variants may contribute to disease etiology, but the impact of a given gene variant may have varied effect size. Here, the authors analyse summary statistics of genome-wide association studies from fourteen cancers, and show the utility of polygenic risk scores may vary depending on cancer type.